2013
DOI: 10.1097/mib.0b013e31828133ad
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Urgent Findings on Abdominopelvic CT in Emergency Department Patients with Crohn’s Disease

Abstract: Background & Aims In the United States, the use of abdominopelvic computed tomography (APCT) by emergency departments for patients with abdominal pain has increased, despite stable admission rates and diagnosis requiring urgent intervention. We proposed that trends would be similar for patients with Crohn's disease (CD). Methods We conducted a retrospective study of data from 648 adults with CD who presented at 2 emergency departments (2001–2009; 1572 visits). Trends in APCT use were assessed with Spearman's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Stricturing or penetrating disease, heart rate [100 beats/min, leukocyte count [10,000/mm 3 , and CRP [2.5 mg/dL were independent predictors of urgent findings on APCT, whereas biologic agent use was a negative predictor of urgent findings. To date, there has been only one study that investigated clinical predictors of urgent findings on APCT in ED patients with CD [13]. In comparison with the previous study, the strength of our study is that we assessed in detail the clinical impact of APCT on non-urgent findings.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Stricturing or penetrating disease, heart rate [100 beats/min, leukocyte count [10,000/mm 3 , and CRP [2.5 mg/dL were independent predictors of urgent findings on APCT, whereas biologic agent use was a negative predictor of urgent findings. To date, there has been only one study that investigated clinical predictors of urgent findings on APCT in ED patients with CD [13]. In comparison with the previous study, the strength of our study is that we assessed in detail the clinical impact of APCT on non-urgent findings.…”
Section: Discussionmentioning
confidence: 83%
“…However, Kerner et al [12] revealed that, despite the increased use of APCT by EDs for patients with CD, there were no significant changes in admission rate or the proportion of APCT with urgent findings. Their studies also reported that, among patients with CD who presented to the ER, only one-third of APCTs were associated with CD-related or non-CD-related urgent findings [12,13]. In other words, two-thirds of patients without urgent findings could potentially have avoided radiation exposure.…”
Section: Introductionmentioning
confidence: 88%
“…This should be based on history and physical findings. In one analysis, a prior history of intestinal obstruction or intraabdominal abscess, current hematochezia, and leukocytosis (WBC count >12,000 lL) were independent predictors of urgent findings on a subsequent CT (abscess, perforation, obstruction, or new or worsening non-Crohn's disease findings) [74]. If the patient presentation warrants immediate imaging, then a CT should be performed.…”
Section: Imaging Crohn's Patients In the Emergency Departmentmentioning
confidence: 96%
“…First, MRE is generally not a practical imaging alternative for emergency department patients. Recent investigations have shown that CT imaging in the emergency setting is very efficacious in identifying important complications of Crohn's disease [71,72,74]. However, before contemplating a CT, risk stratification should be performed by the ordering physician.…”
Section: Imaging Crohn's Patients In the Emergency Departmentmentioning
confidence: 98%
See 1 more Smart Citation